Український поет із Румунії Кирило Куцюк-Кочинський у світлі мемуарів та поетичного самовираження - Ковалець, Л. (Слово і Час, 2018)
У статті здійснено спробу наукового першопрочитання життєвої історії та поетичної спадщини
Кирила Куцюка-Кочинського (1910 – 1991). Народжений в Україні, за фахом інженер, він під
час Другої світової війни опинився в Румунії, де й прожив до останку; дебютував у літературі
1974 р. Лірика К. Куцюка-Кочинського, як і створена на основі гомерівського епосу фантастична
поема “Довге блукання Одіссея” мають автобіографічний підтекст. Вони збагатили українське
письменство показом складного внутрішнього світу людини, її суб'єктивних, багато в чому
індивідуальних переживань. Батьківщину, рідне поет-емігрант сприймав як фундаментальні
цінності, відповідно і страждання, пов'язані з ними, стали провідним лейтмотивом творчості. The paper offers the first attempt of summarizing and interpreting the life history and poetic heritage
of Kyrylo Kutsiuk-Kochyns’kyi (1910–1991). Born in Ukraine, a qualified engineer, at the time of the
Second World War he found himself in Romania and lived there to the end. The researcher traces
the formation of human and creative individuality of this author, his patriotic sentiments, humanistic
beliefs, artistic and aesthetic tastes, his reading interests, as they significantly influenced the writer’s
self-expression. Debuting in 1974, K. Kutsiuk-Kochynskyi worked intensely in the field of writing and
published more than a dozen books. They enriched the Ukrainian poetry with complex, metaphorical,
maybe sometimes excessively complicated presentation of the inner world of a person in exile, full of
peculiar and often very individual and subjective associations. It is a lyric of feeling, but also thoughts,
although almost without descriptive or narrative components. Kutsiuk-Kochynskyi also worked as a
translator. This part of his legacy includes a wide range of historical and literary works that represent
a literature of many foreign countries.
K. Kutsiuk-Kochynskyi’s poem “Long Wanderings of Odysseus” (1988) stands separately as a kind
of autobiography and vivid literary reflection. The traditional (Homeric) plot, motifs and images of the
original were rethought in accordance with the new sociocultural reality of the 20th century. They were
compared with his own life path shown as a myth. Writing down this myth and the history in the all-
Ukrainian and world dimension, the author thus expressed a number of overwhelming problems. They
relate to war and peace, the moral, existential essence of man, his life, existential choice, complex
relations with other people and civilization.
There is a need to republish in Ukraine at least the selected works by K. Kutsiuk-Kochynskyi, which
would contribute to faster return of this writer to his proper place in Ukrainian literature. В статье предпринята попытка научного первопрочтения
жизненной истории и поэтического наследия Кырыла
Куцюка-Кочинского (1910–1991). Рожденный в Украине,
по специальности инженер, он во время Второй мировой
войны был заброшен судьбой в Румынию, где и прожил
до смерти, в литературе дебютировал 1974 г. Лирика
К. Куцюка-Кочинского, как и созданная на основе
гомеровского эпоса фантастическая поэма “Долгое
блуждание Одиссея”, имеют автобиографический
подтекст, они обогатили украинскую литературу показом
сложного внутреннего мира человека, его субъективных,
во многом индивидуальных переживаний. Родина, родное
воспринимались поэтом-эмигрантом как фундаментальные
ценности, соответственно и страдания, связанные с ними,
стали ведущим лейтмотивом творчества.